2017
DOI: 10.1007/s10549-017-4146-3
|View full text |Cite
|
Sign up to set email alerts
|

Complications and thromboembolic events associated with tamoxifen therapy in patients with breast cancer undergoing microvascular breast reconstruction: a systematic review and meta-analysis

Abstract: Purpose Tamoxifen therapy is integral in the treatment of patients with hormone receptor-positive breast cancer. However, there is an association between tamoxifen and thromboembolic events. Flap and systemic thromboembolic events have devastating consequences in microvascular breast reconstruction. Currently, there is conflicting data on the association between tamoxifen therapy and thromboembolic complications for patients undergoing microvascular breast reconstruction. The objective of this study is to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Although other risk factors, such as radiotherapy or obesity, are discussed in the literature, we could not prove an influence of previous radiation therapy or a BMI of >30 kg/m 2 on vesselassociated complications (32)(33)(34)(35). Furthermore, flap failure was not associated with venous thrombosis underlining the superiority of venous coupler systems compared to handsewn anastomoses (23,30,36).…”
Section: Discussionmentioning
confidence: 67%
“…Although other risk factors, such as radiotherapy or obesity, are discussed in the literature, we could not prove an influence of previous radiation therapy or a BMI of >30 kg/m 2 on vesselassociated complications (32)(33)(34)(35). Furthermore, flap failure was not associated with venous thrombosis underlining the superiority of venous coupler systems compared to handsewn anastomoses (23,30,36).…”
Section: Discussionmentioning
confidence: 67%
“…Results of previous studies have been conflicting, and there is no consensus on the timing for the suspension of hormone treatment prior to reconstructive surgery. [11][12][13][14][15][16][17][18] The increasing adoption of extended endocrine treatments and the increasing number of patients undergoing reconstructive surgery provide an imperative to determine the balance of benefits and risks of perioperative hormonal therapy in the reconstructive setting, particularly when microvascular techniques are employed. 6 , 8 This retrospective study of 233 patients has revealed neither an increased risk of flap complications nor thromboembolic events in patients receiving hormone therapy (either tamoxifen or AIs), within one month prior to breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…12 , 14 , 15 , 17 , 18 The current study was prompted by an analysis of four studies by Parikh et al involving 1700 patients and 2245 procedures. 13 These authors concluded that breast cancer patients receiving perioperative tamoxifen therapy, as compared to those who were not, have an increased risk of thrombotic flap complications (including total flap loss) following microvascular breast reconstruction. 13 Results from the present, albeit much smaller, study do not support these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being so, the random start COS prevents the delay to start chemotherapy, and the concomitant use of letrozole and tamoxifen may help to make the procedure safer. It is known that there is an association between tamoxifen therapy and thromboembolic events [ 31 ]. Furthermore, considering the possibility of venous thromboembolism as a paraneoplasic syndrome, we propose the prophylactic administration of enoxaparin in order to prevent this complication.…”
Section: Discussionmentioning
confidence: 99%